(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article contains the evaluation of the effectiveness of the methods of detecting vulnerabilities and network attacks, the recommendations proposed by the Cyber Security Center to increase the effectiveness of the detection of vulnerabilities and network attacks and the provision of information security, the results of the three-step testing method for detecting vulnerabilities on servers, the results of the evaluation of the effectiveness of the VITE method of detecting network attacks given.